Leading in a culture of change - Fullan, Michael (Jossey-Bass, 2020)
"Good leadership is not innate. One must learn to lead by mastering five core competencies -- attending to moral purpose, understanding the change process, building relationships, sharing knowledge, and creating coherence in their organizations. The second edition of Leading in a Culture of Change, will contain new case examples of developing and applying the core concepts in practice. Readers will learn what success looks like and how to lead organizations to success using the core concepts. This edition will define the core concepts with greater precision and depth along with concrete examples from the present. Business, nonprofit, and public sector leaders are facing new and daunting challenges -- rapid-paced developments in technology, sudden shifts in the marketplace, and crisis and contention in the public arena. This book provides insights into the dynamics of change and the role of leadership in managing and coping with the change process. Leadership today requires the ability to mobilize constituents to do important but difficult work under conditions of constant change, overload, and fragmentation. This book shows leaders how they can effectively accomplish their goals -- by attending to their broader moral purpose, keeping on top of the change process, cultivating relationships, sharing knowledge, and setting a vision and context for creating coherence in their organization"--